Cardiovascular Risk Factors and Cognition in Older Adults at High Risk of Alzheimer's Disease Following a Lifestyle Multimodal Intervention: An Assessment of the PENSA Study. (14th June 2022) - Belhaj, Mariam; Soldevila-Domenech, Natalia; Forcano, Laura; Cuenca-Royo, Aida; Fagundo, Beatriz; Boronat, Anna; Lorenzo, Thais; Piera, Iris; Diaz-Pellicer, Patricia; de Toma, Ilario; Fauria, Karin; Molinuevo, Jose Luis; et al.
Abstract: Objectives: We aimed to evaluate the association between cardiovascular risk factors and cognition in individuals at high risk of Alzheimer's disease following 12 months of personalized multimodal intervention for preventing cognitive decline (PENSA Study), which includes Mediterranean diet, physical activity, cognitive training, psychoeducational, and social stimulation. Methods: We report preliminary analyses of N = 128 older adults (64.1% women, aged 60–80 years) APOE -ɛ4 carriers meeting subjective cognitive decline criteria. Following the FINGER Study inclusion criteria, the CAIDE score was calculated and a cut-off point of ≥6 was established to identify individuals at high risk of dementia. Using the Pearson's r coefficient, we evaluated the baseline association and the 6-months correlated change (in sub-sample of N = 46 subjects) between cardiovascular factors and several cognitive tests, including the MoCA and the gold-standard Preclinical Alzheimer's disease Cognitive Composite (ADCS-PACC) and a modified version of this composite, the ADCS-PACC-plus-exe. Gender differences were also evaluated. Results: At baseline, higher fasting plasma glucose, glycosylated hemoglobin, triglycerides, abdominal circumference, and lower HDL-cholesterol, were associated with high dementia risk (P < 0.05). There was also a negative linear association between the CAIDE score and the MoCA (r = −0.26, P = 0.012), the ADCS-PACC (r = −0.23, P = 0.026) and the ADCS-PACC-plus-exe (r = −0.25, P = 0.018). After 6 months, the median CAIDE score decreased, (P < 0.05) in both gender. Median systolic and diastolic blood pressure, glucose, total cholesterol, and triglyceride levels were also reduced in the overall population, but greater reductions were observed in men. Moreover, 6-months change in CAIDE score was negatively associated with changes in the ADCS-PACC in men (r = −0.57, P = 0.013), but this association was positive in women (r = 0.45, P = 0.031). Conclusions: After 6 months of multimodal intervention, the cardiovascular profile of participants improved, in parallel with their cognitive performance. However, important gender differences emerged were observed. Funding Sources: Alzheimer Association (18PTC-R-592, 192) and Instituto de Salud Carlos III (ISCIII PI17/00, 223). CIBERFES and CIBEROBN are initiatives of the Instituto de Salud Carlos III by the FEDER fund.